Application of Microbial Biotechnology for the Treatment of Organic Pollutants and Heavy Metals in Wastewater - Raghda Saad Jameel (Jurnal MIPA dan Pembelajarannya, 2026)
One of the biggest environmental problems of the contemporary world is wastewater pollution caused by the fast urbanization process and the industrial growth. The traditional wastewater treatment methods are characterized by the fact that they are very costly to run and that they are not very efficient in eliminating the complex pollutants. The modern biotechnology presents viable substitutes by applying microorganisms, enzymes, and bio systems that have the capacity of degrading contaminants. This paper examines the application of microbial biotechnology in the de-contamination of wastewater of organic pollutants and heavy metals. An experimental investigation was carried out in laboratory scale incorporating microbial consortia that was conducted in controlled conditions in a treatment period of 30 days. The outcome showed that there were substantial biochemical oxygen demand (BOD) and chemical oxygen demand (COD) and heavy metal reduction. These results validate that biotechnological wastewater treatment systems are sustainable wastewater management systems which are environmentally friendly, cost-effective and efficient.